Nebria (Paranebria) livida ... - Sundukov, Yurii N.; Novomodnyi, Evgeniy V. (Zenodo, 2022)
Nebria (Paranebria) livida (Linnaeus, 1758) Material. Khabarovsk, bank of the Amur Channel, May 2000, E. Novomodnyi leg., 1♀. Distribution. A subboreal transpalearctic species: from France and Norway in the west to Primorsky Region and the Japanese Islands in the east, from the Scandinavian Peninsula, the Khanty-Mansiysk Autonomous Region, the south of Eastern Siberia and Amur Region in the north to Altai, Central Mongolia, Northeast China, South Korea, and Kyushu Island in the south; listed for southwest of Kazakhstan (the Ili River valley) (Kolov 2002). ... : Published as part of Sundukov, Yurii N. & Novomodnyi, Evgeniy V., 2022, Ground beetles (Coleoptera, Carabidae) of Khabarovsky Region in the collection of Grodekov Khabarovsk Regional Museum, pp. 570-593 in Amurian Zoological Journal XIV (4) on page 572, DOI: 10.33910/2686-9519-2022-14-4-570-593, http://zenodo.org/record/12815734 ...